1993
DOI: 10.1182/blood.v81.10.2688.2688
|View full text |Cite
|
Sign up to set email alerts
|

Nasal T-cell lymphoma: a clinicopathologic entity associated with peculiar phenotype and with Epstein-Barr virus

Abstract: Recent evidence has shown that most nasal lymphomas (NL) are associated with a T-cell phenotype and are thus called nasal T-cell lymphomas (NTCL), but little information is available about the T-cell receptor (TCR) expression. The presence of Epstein-Barr virus (EBV) genome has been recently reported in NTCL in Oriental populations in which NL and EBV-associated tumors are more common and in occasional Occidental cases. This prompted us to investigate lymphoma biopsies from 7 non- Oriental patients with NTCL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(99 citation statements)
references
References 45 publications
6
89
1
3
Order By: Relevance
“…Interestingly, Jaffe et al 17 described rare cases that may present in the skin or soft tissue and relapse in the nose. In our review of the literature between 1983 and 1996, we found only 17 clear cases, 3,7,8,11,18,[21][22][23][24][25][26][27][28] of peripheral T-cell lymphoma with skin as well as nose metastasis. In six cases, 7,18,23,27,28 the lymphoma clearly proceeded from the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jaffe et al 17 described rare cases that may present in the skin or soft tissue and relapse in the nose. In our review of the literature between 1983 and 1996, we found only 17 clear cases, 3,7,8,11,18,[21][22][23][24][25][26][27][28] of peripheral T-cell lymphoma with skin as well as nose metastasis. In six cases, 7,18,23,27,28 the lymphoma clearly proceeded from the skin.…”
Section: Discussionmentioning
confidence: 99%
“…1-10 NKTCL shows high prevalence in people of Asian decent and commonly presents with midline facial destructive disease. [1][2][3][4][5] Morphologically, NKTCL is characterized by a broad cytological spectrum; the atypical cells may be small or medium-sized cells, large atypical and hyperchromatic cells or a mixture of these types with coagulation necrosis of dermis and subcutis. Virtually all cases of NKTCL are positive for EBV.…”
Section: Reportmentioning
confidence: 99%
“…Because the nasal area is the most common site of presentation and CD56+ NK cells expressing T-cell immunophenotype are the most likely lineage, nasal NKTCL has been thought to be an appropriate term. [1][2][3][4][5] Tumours with identical morphology, immunophenotype, and genotype presenting in extra-nasal areas were given the name of nasal type NKTCL. 9,10 Nasal NKTCL is mostly localized to the nasal areas but shows a propensity to spread or recur in the certain predilection sites such as skin, palate, tonsil, testis, gastrointestinal tract and other soft tissues.…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Epstein-Barr virus (EBV) is associated with various lymphoid malignancies, including Burkitt's lymphoma, 1) lymphoma occurring in immunocompromised patients, 2) Hodgkin's disease, 3) pyothorax-associated lymphoma, 4,5) nasal and nasal type T/Natural Killer (T/NK) cell lymphoma (NT/NKL), 6) NK cell leukemia/lymphomas, [7][8][9] Tcell lymphoma, 10) and a few other lymphoma subtypes. B cell lymphoma predominates in EBV-associated lymphomas, while some portions are reported to be of T and/or NK cell lineage.…”
Section: Abstract: Lymphoma -Epstein-barr Virus -T Cell -Chromosomalmentioning
confidence: 99%